Continuous lateral rotational therapy in trauma—A systematic review and meta-analysis. Issue 5 (November 2017) - Schieren, Mark; Piekarski, Florian; Dusse, Fabian; Marcus, Hanke; Poels, Marcel; Wappler, Frank; Defosse, Jérôme
Abstract : BACKGROUND: The purpose of this study was to evaluate the impact of continuous lateral rotational therapy (CLRT) on respiratory complications and mortality in patients suffering from trauma. METHODS: The literature databases PubMed®/Medline® and the Cochrane Library® were systematically searched for prospective controlled trials comparing continuous lateral rotational therapy to conventional manual positioning in trauma patients. RESULTS: A total of 8 publications (n= 422 patients) with comparable age and injury severity were included in the meta-analysis. A significant reduction in the incidence of nosocomial pneumonia (OR: 0.33, [95%CI: 0.17, 0.65], p=0.001) was observed in patients treated prophylactically with continuous lateral rotational therapy. When used with therapeutic intention, CLRT had no impact on the incidence of pneumonia. There were no significant differences in mortality, duration of mechanical ventilation, or ICU length of stay. CONCLUSIONS: Analogous to studies evaluating CLRT in medical or mixed patient collectives, CLRT reduced the rates of nosocomial pneumonia in trauma patients. This, however, had no impact on overall mortality. The level of evidence of the studies included was limited by several factors. An adequately powered, well-designed multi-centre randomised controlled trial is required, to validly assess the utility of CLRT for the prevention and treatment of pulmonary complications in patients suffering from trauma. LEVEL OF EVIDENCE: Systematic review and meta-analysis, level III.